Psychometric properties of the European Portuguese version of the Perceived Risk of HIV Scale in the general population and HIV-uninfected partners from sero-different couples - Alexandra Martins; Catarina Chaves; Maria Cristina Canavarro; Marco Pereira (BMC, 2019)
Abstract Background Perceived risk of HIV plays an important role in the adoption of protective behaviours and HIV testing. However, few studies have used multiple-item measures to assess this construct. The Perceived Risk of HIV Scale (PRHS) is an 8-item measure that assesses how people think and feel about their risk of HIV infection. This cross-sectional study aimed to assess the psychometric properties (reliability and validity) of the European Portuguese version of the PRHS, including the ability of this scale to discriminate between individuals from the general population and HIV-uninfected partners from sero-different couples on their perceived risk of HIV infection (known-groups validity). Methods This study included 917 individuals from the general population (sample 1) to assess the psychometric properties of the PRHS. To assess the known-groups validity, the sample comprised 445 participants from the general population who were in an intimate relationship (sub-set of sample 1) and 42 HIV-uninfected partners from sero-different couples (sample 2). All participants filled out a set of questionnaires, which included a self-reported questionnaire on sociodemographic information, sexual behaviours, HIV testing and the PRHS. Sample 1 also completed the HIV Knowledge Questionnaire - 18-item version. Results The original unidimensional structure was reproduced both in exploratory and confirmatory factor analyses, and the PRHS demonstrated good reliability (α = .78; composite reliability = .82). The differential item functioning analyses indicated that the items of the PRHS, in general, did not function differently for men and women or according to HIV testing. Significant associations with sexual risk behaviours and HIV testing provided evidence for criterion validity. The known-groups validity was supported. Conclusions The PRHS is a suitable scale in the evaluation of the perceived risk of HIV, and its psychometric characteristics validate its use in the Portuguese population. Furthermore, the present study suggests that interventions improving individuals' HIV risk perceptions may be important since they were associated with different sexual behaviours and the likelihood of HIV testing.